2016
DOI: 10.1021/acsnano.6b03159
|View full text |Cite
|
Sign up to set email alerts
|

DNA Translocation through Nanopores at Physiological Ionic Strengths Requires Precise Nanoscale Engineering

Abstract: Many important processes in biology involve the translocation of a biopolymer through a nanometer-scale pore. Moreover, the electrophoretic transport of DNA across nanoscale pores is under intense investigation for single-molecule DNA sequencing and analysis. Here we show that the precise patterning of the entry and the middle section of the ClyA nanopore with positive charges are crucial to observe the electrophoretic translocation of DNA at physiological ionic strength. Surprisingly, the strongly electronega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 59 publications
6
76
0
Order By: Relevance
“…Owing to its evolving importance as a nanopore sensor for proteins48 and DNA49, and the possibility to engineer its size and properties50, we chose ClyA as the model nanopore to test our system. The encapsulated bilayer could be functionalized with ClyA pores by incorporating the oligomeric pore inside the aqueous droplet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its evolving importance as a nanopore sensor for proteins48 and DNA49, and the possibility to engineer its size and properties50, we chose ClyA as the model nanopore to test our system. The encapsulated bilayer could be functionalized with ClyA pores by incorporating the oligomeric pore inside the aqueous droplet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, it is often determined by placing the pore in a salt gradient (i.e., different salt concentrations in the cis and trans reservoirs) and measuring the potential at which the nanopore current is zero (reversal potential, V r ). 96,101 The Goldman-Hodkin-Katz (GHK) equation can then be used to convert V r into the permeability ratio P Na + = G Na + /G Cl − . Here, we represent the ClyA's ion selectivity (Figs.…”
Section: Transport Of Ions Through Clyamentioning
confidence: 99%
“…Using the reversal potential method, Franceschini et al 101 found ClyA's ion selectivity to be t Na + = 0.66 (P Na + = 1.9). In our ePNP-NS simultation, this corresponds the selectivity at c s = 0.5 M (at V b = 0 mV), a value that lies in between the cis (1 M, t Na + = 0.57, concentrations.…”
Section: Transport Of Ions Through Clyamentioning
confidence: 99%
See 1 more Smart Citation
“…[7]. In this paper we analyze the capture of both ssDNA and dsDNA by Cytolysin A (ClyA), a biological nanopore which has been recently employed both for nucleic acid and protein analysis [3,9,4,11]. In experiments, DNA molecules are initially placed in the cis-side of the membrane.…”
Section: Introductionmentioning
confidence: 99%